2005
DOI: 10.1002/pssc.200460552
|View full text |Cite
|
Sign up to set email alerts
|

Optical characterization of crystalline silicon embedded in a‐Si matrix

Abstract: The photoluminescence of pure amorphous Si films and films with embedded Si quantum dots and large nano-crystallites is correlated with XRD and AFM measurements. Several PL bands in the IR spectral range with maxima at 0.90, 0.98, 1.18 and 1.39 eV have been revealed in studied samples. The 0.90-0.98 eV PL bands are attributed to band tail luminescence in Si nano-crystallites. Concurrently, the 1.18 and 1.39 eV PL bands are assigned to radiative transitions between quantum confined levels within Si quantum dots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…These elementary PL bands could be attributed to amorphous silicon and Si NCs as well as to defects in the glass substrate. The comparative investigation of PL spectra of amorphous films and glass substrates confirmed that 1.75 eV PL band originates from the defects in glass substrate [11]. PL spectra measured at 300 K for second group of films prepared at 300°C substrate temperature and different filament temperatures are shown in Fig.…”
Section: Resultsmentioning
confidence: 51%
“…These elementary PL bands could be attributed to amorphous silicon and Si NCs as well as to defects in the glass substrate. The comparative investigation of PL spectra of amorphous films and glass substrates confirmed that 1.75 eV PL band originates from the defects in glass substrate [11]. PL spectra measured at 300 K for second group of films prepared at 300°C substrate temperature and different filament temperatures are shown in Fig.…”
Section: Resultsmentioning
confidence: 51%
“…It is shown earlier [9] that the size of Si nc in amorphous Si films increased from 2.5 up to 20 nm with the increase of Fig. 4(b)) and its spectral shift correlates with the temperature shrinkage of silicon band gap as well.…”
Section: Resultsmentioning
confidence: 80%
“…The gases flowed through the 0.75 mm diameter and 13 cm long coiled tungsten filament. The variation of substrate or filament temperatures allows obtaining amorphous Si films with Si nc sizes from the range 2.5 up to 20 nm, respectively [9].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Si NCs embedded in amorphous matrix. The matrix could be the silicon oxide [1,2], or silicon nitride [3], or amorphous silicon (a-Si) [4].…”
Section: Introductionmentioning
confidence: 99%